2022
DOI: 10.1038/s41598-022-22381-z
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of sleep/wake disturbances in a progressive macaque model of Parkinson’s disease

Abstract: Parkinsonian patients often experience sleep/wake disturbances, which may appear at an early stage of the disease; however, these disturbances have not been fully described. To better understand the evolution of these disturbances with respect to disease progression, we aimed to characterize these clinical signs in a progressive nonhuman primate model of Parkinson's disease. Three adult macaques (Macaca fascicularis) were equipped with a polysomnographic telemetry system allowing the characterization of sleep/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…The NHPs exhibited significant altered wake/sleep behavior in the parkinsonian state compared to the healthy state (as already described in different NHP model of PD 30 , 31 , 33 and also observed in patients with advanced PD 34 , 35 ). MPTP-treated animals showed EDS, characterized by a decrease in sleep latency, an inability to maintain long periods of wakefulness, and prominent disorganization of naps.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The NHPs exhibited significant altered wake/sleep behavior in the parkinsonian state compared to the healthy state (as already described in different NHP model of PD 30 , 31 , 33 and also observed in patients with advanced PD 34 , 35 ). MPTP-treated animals showed EDS, characterized by a decrease in sleep latency, an inability to maintain long periods of wakefulness, and prominent disorganization of naps.…”
Section: Discussionsupporting
confidence: 73%
“…However, the MPTPtreated NHPs model exhibited sleep/wake disturbances similar to that observed in PD patients. Thus, MPTP-treated NHPs experience disorganization of nighttime sleep with reduced sleep quality and EDS characterized by sleep episodes occurring more rapidly in the morning and spreading through the middle of the day, as described in a recent study conducted by our group 33 and others 30,31,55 . We also acknowledge the limited number of animals used in the present study, due to ethical considerations concerning animal use; however, our results were consistent across animals.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…After recordings of the baseline during the healthy state, monkeys were chronically intoxicated by intramuscular injections of MPTP under light anesthesia (Ketamine 2-4 mg/kg), based on a previous study (Davin et al, 2022). This progressive protocol, allowing a long non-motor phase to mimic the clinical pathology, consisted in small injections of MPTP (0.2-0.5 mg/kg, in NaCl 0.9%) every two weeks until the parkinsonian syndrome was stable.…”
Section: Mptp Treatmentmentioning
confidence: 99%
“…While several human and NHP studies have demonstrated that SWS is disrupted in advanced parkinsonism 11,22,23 , whether SWS dysfunction occurs during the early phase of dopaminergic system degeneration is not clear in the literature. A comparison of SWS in idiopathic REM sleep behavior disorder (RBD, often a prodromal stage of PD) patients and healthy controls have shown variable results [24][25][26][27][28] .…”
mentioning
confidence: 99%